Circadian gene expression in peripheral blood leukocytes of rotating night shift nurses - Edyta Reszka; Beata Peplonska; Edyta Wieczorek; Wojciech Sobala; Agnieszka Bukowska; Jolanta Gromadzińska; Jenny-Anne Lie; Helge Kjuus; Wojciech Wasowicz (Nordic Association of Occupational Safety and Health (NOROSH), 2013)
OBJECTIVE: It has been hypothesized that the underlying mechanism of elevated breast cancer risk among long-term, night-working women involves circadian genes expression alteration caused by exposure to light at night and/or irregular work hours. The aim of the present study was to determine the effect of rotating night shift work on expression of selected core circadian genes. METHODS: The cross-sectional study was conducted on 184 matched nurses and midwives, who currently work either day or rotating night shifts, to determine the effect of irregular work at night on circadian gene expression in peripheral blood leukocytes. Transcript levels of BMAL1, CLOCK, CRY1, CRY2, PER1, PER2, and PER3 were determined by means of quantitative real-time polymerase chain reaction (PCR). RESULTS: After adjusting for hour of blood collection, there were no statistically significant changes of investigated circadian genes among nurses and midwives currently working rotating night shifts compared to nurses working day shifts. The highest expression of PER1 messanger ribonucleic acid (mRNA) was observed for women currently working shifts who had worked >15 years in rotating night shift work. PER1 gene expression was associated with the lifetime duration of rotating night shift work among women currently working night shifts (P=0.04). PER1 and PER3 transcript levels in blood leukocytes were significantly down-regulated in the later versus early hours of the morning between 06.00-10.00 hours (β-coefficient -0.226, P=0.001 and β-coefficient -0.181, P<0.0001, respectively). CONCLUSIONS: These results suggest that current rotating night shift work does not affect circadian gene expression in human circulating leukocytes. In analysis of the peripheral clock in human studies, the hour of blood collection should be precisely specified.